Chapter 5 Alchemy, potency, imagination Paracelsus's theories of poison - Hedesan, Georgiana D. (Taylor & Francis, 2018)
A case in point is Paracelsus's view of poisons, which have a richness that has not been captured in previous scholarship. Most scholars only touched on the subject of poison and did not fully reflect on the complexity of its meaning. Consequently, I have decided to explore Paracelsus's ideas and bring together the various connotations he conferred to the term 'poison'. For the purpose of this chapter, I have chosen a methodology that would take account of the timing of Paracelsus's writings as well as their relevance to the subject at hand. I have consequently decided to take a treatise-based approach that would not only focus on works that have a particular emphasis on the topic of poison, but also reflect, to the best extent possible, the chronology of these treatises. The chapter is thus focussed on seven writings, although it makes references to other works where appropriate. At the end, I have tried to synthesise the views of these works and consider the question of consistency of ideas on 'poison' throughout Paracelsus's writings.